The final battle! Variability of performance of finalists in world judo championships - Agostinho, M.; Kons, R.; Franchini, E. (The Arts and Sciences of Judo, 2025)
The aim of this study was to investigate the technical variability of gold and silver medallist athletes who competed in the 2022 and 2023 judo world championships across different age categories (cadets, juniors, seniors) and sexes (male, female). The analysis included 176 finalist athletes, focusing on techniques, directions of kuzushi (breaking balance), grip configurations, actions before attacking (tachi-waza), and transitions to groundwork (ne-waza). The Kruskal-Wallis test was used to compare groups, followed by Dunn`s post hoc comparisons, with the significance level set at 5%. Concerning sex, results indicated that males exhibit higher standing combat variability (p<0.01), while females presented greater groundwork variability (p<0.05). Gold medallists demonstrated higher variability in pre-attack actions and throwing techniques compared to silver medal winners (p<0.05). However, there was no effect of age categories (p > 0.05). These findings revealed distinct differences in scoring actions between male and female world championship finalists, highlighting characteristics that are extremely specific to athletes who reached the highest place on the podium in high-level competition, considering the variability of judo techniques.